2020
DOI: 10.1364/prj.8.000127
|View full text |Cite|
|
Sign up to set email alerts
|

Erbium-doped TeO2-coated Si3N4 waveguide amplifiers with 5  dB net gain

Abstract: We demonstrate 5 dB net gain in an erbium-doped tellurium-oxide-coated silicon nitride waveguide. The amplifier design leverages the high refractive index and high gain in erbium-doped tellurite glass as well as the ultra-low losses and mature, reliable, and low-cost fabrication methods of silicon nitride waveguide technology. We show that the waveguide platform demonstrates low background propagation losses of 0.25 dB/cm based on a ring resonator device with a Q factor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Amorphous host materials can typically be deposited at the wafer level leading to simpler fabrication and integration schemes. Several host materials have been demonstrated, including Ta 2 O 5 doped with both Er 3 and Yb 3 [30], TeO 2 doped with Er 3 [31] and Tm 3 [32], and Al 2 O 3 doped with Nd 3 , Yb 3 , Er 3 , Tm 3 , and Ho 3 [19,25,[33][34][35] to achieve emission at different wavelengths. Those materials are mainly deposited by reactive co-sputtering, although recent studies on rare-earth-ion-doped Al 2 O 3 deposited by atomic layer deposition have shown very high gain per unit length (i.e., 20.1 7.31 dB∕cm net modal gain in Al 2 O 3 :Er 3 ) [23] thanks to the control of Al 2 O 3 and Er 2 O 3 at the sub-atomic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amorphous host materials can typically be deposited at the wafer level leading to simpler fabrication and integration schemes. Several host materials have been demonstrated, including Ta 2 O 5 doped with both Er 3 and Yb 3 [30], TeO 2 doped with Er 3 [31] and Tm 3 [32], and Al 2 O 3 doped with Nd 3 , Yb 3 , Er 3 , Tm 3 , and Ho 3 [19,25,[33][34][35] to achieve emission at different wavelengths. Those materials are mainly deposited by reactive co-sputtering, although recent studies on rare-earth-ion-doped Al 2 O 3 deposited by atomic layer deposition have shown very high gain per unit length (i.e., 20.1 7.31 dB∕cm net modal gain in Al 2 O 3 :Er 3 ) [23] thanks to the control of Al 2 O 3 and Er 2 O 3 at the sub-atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present an integrated high total gain (i.e., from passive waveguide to passive waveguide) optical amplifier in Al 2 O 3 :Er 3 monolithically integrated onto the Si 3 N 4 platform via a double-layer platform [38]. Different from previous integration methodologies in which the Al 2 O 3 :RE 3 material was directly deposited onto Si 3 N 4 elements [20,21,23,31] or sputtered into SiO 2 trenches within the Si 3 N 4 platform [19,22], in our approach the Al 2 O 3 :RE 3 and the Si 3 N 4 waveguides are located in two individual layers separated by a thin SiO 2 film. The optical modes are therefore guided independently in each of the photonic layers permitting their independent optimization to minimize losses and to maximize the overlap between pump and signal modes on the active waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Such a device not only is useful as a stand-alone highly nonlinear system but can also enhance the nonlinearity of the existing Si 3 N 4 waveguides postfabrication. Together with the emerging integrated lasers and amplifiers on TeO 2 and other rare-earth media [47][48][49]24,25], this work paves the way for a monolithic TeO 2 -based nonlinear silicon photonics platform.…”
Section: Introductionmentioning
confidence: 93%
“…To optimize the performance of erbium-based integrated amplifier devices, various host materials and different fabrication methods have been studied to achieve high erbium-incorporation inside different compounds [7][8][9][10][11][12][13][14][15][16][17][18][19]. Additionally, unique waveguide geometries have also been proposed to maximize the interaction of the guided beams with the active layer [20][21][22][23][24][25]. Despite the recent progress in the field, there is still a relatively long way to go before erbium-based integrated devices can be established as fundamental active building blocks in the silicon photonics industry.…”
Section: Introductionmentioning
confidence: 99%